DEVELOPMENT OF WAQF MANAGEMENT IN JORDAN - Maryam Batubara; Mukhlis (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
Waqf is one of the teachings of Islam and has been known since the time of the Prophet SAW. There are two opinions about who was the first to implement waqf. The first opinion, some scholars say, is that the first person to implement waqf law was Rasulullah SAW, where he donated his land to later build the Quba mosque when Rasulullah moved to Medina. The Quba Mosque was built in 622, located about 400 kilometers north of the city of Makkah. During the leadership of King Abdullah II, the law on waqf and Islamic affairs was revised again and became law number 32 of 2011 with the same name. The spirit is to utilize the potential of waqf so that it can be maximized in line with current developments. The message contained in law number 32 of 2011 is, first, the Ministry of Waqf for Islamic Affairs and Holy Places and Islamic Affairs is institutionally and financially independent in order to develop and invest waqf assets. Development of Endowment Funds in Jordan 50% of the foundation's income is used for places of worship and other needs. Meanwhile, the other 50% of income is distributed to four other charities (poverty, disease, education and society).